Features cell cycle rat hepatocytes under the experimental hypothyroidism and hyperthyroidism - Rykalo, N. A.; Mordvinova, O. M.; Vasilets, Y. O. (Journal of Education, Health and Sport, 2017)
Thyroid hormones are necessary for normal development, growth and functioning of organs. The experiment investigated the changing phases of the cell cycle of liver cells in rats under simulatedhypothyroidism and hyperthyroidism. The experiment was conducted on 40 white laboratory rats with body mass 120-150g. The animals were divided into groups: №1 - 15 animals - model hypothyroidism, administration Merkazolil 10 mg / kg, №2 - 15 animals - model hyperthyroidism due tointroduction of the L-thyroxine 200 mg / kg. Drugs were administered intragastric with 1% starch slurry once a day. Group №3, control - 10 rats wereinjected only solvent. After the withdrawal of animals from the experiment by decapitation under ketaminanesthesia, part of the liver size 1x1 cm was removedfromsame location. Cytofluorometric analysis was conducted on the multifunctional research flow cytometer "PartecPAS" company Partec (Germany) SIC VNMU named after Pirogov. In experimental hypothyroidism significant increase of the number of cells in a state of apoptosis and reduced proliferation activity was observed compared to controls. In experimental hyperthyroidism growing number of nuclei of cells in a state of apoptosis and increased proliferation activity wasobserved compared to controls, this indicats activation of reparative regeneration processes.